2013
DOI: 10.1097/hcr.0b013e3182930cbb
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Psychometric Properties of the Greek Version of the Minnesota Living With Heart Failure Questionnaire

Abstract: This study provides support for the reliability and validity of the Greek version of the MLHFQ.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
19
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 11 publications
3
19
0
Order By: Relevance
“…Regarding construct validity, we found that the three factors explain 47.7% and 54.03% of the overall score in the Rasch analysis and PCA, respectively, with similar results previously reported by another study 27 , while in other studies the variance explained by these three factors has been higher (64.1 to 72%) 9,10,19,28 . Also, we found the following similarities with other authors; Heo, et al 27 evidenced that items (1 and 9) were loaded on physical dimension and items (14 and 16) presented loading <0.4.…”
Section: Interpretation Of Findingssupporting
confidence: 90%
See 1 more Smart Citation
“…Regarding construct validity, we found that the three factors explain 47.7% and 54.03% of the overall score in the Rasch analysis and PCA, respectively, with similar results previously reported by another study 27 , while in other studies the variance explained by these three factors has been higher (64.1 to 72%) 9,10,19,28 . Also, we found the following similarities with other authors; Heo, et al 27 evidenced that items (1 and 9) were loaded on physical dimension and items (14 and 16) presented loading <0.4.…”
Section: Interpretation Of Findingssupporting
confidence: 90%
“…The Minnesota Living with Heart Failure Questionnaire (MLHF-Q) is a disease-specific instrument, consisting of 21 items addressing a wide range of HRQoL and it is the most frequently used internationally. Since 1987, the MLHF-Q has been translated into more than 30 languages, including Spanish [8][9][10][11][12][13] and it is used as an outcome measure in multiple clinical trials showing the best psychometric properties as to validity, reliability and sensitivity to change [14][15][16][17] .…”
Section: Introductionmentioning
confidence: 99%
“…15,16 Discriminant validity of the Gr9-EHFScBS was assessed by calculating the Spearman rank correlation coefficient between the total score of the Gr9-EHFScB and the total score of MLHFQ, assuming that there should only be relatively low association between them, since the MLHFQ measures HF related QoL. 11,12 Though it can be argued that there is an indirect linkage between the variables of self-care and QoL, the associations are not expected to be strong as they are measuring different constructs.…”
Section: Discussionmentioning
confidence: 99%
“…11 The Greek version of the MLHFQ has been shown to measure patients' total HR-QoL as well as three separate sub-dimensions (physical, emotional and social subscales). 12 …”
Section: Other Instrumentsmentioning
confidence: 97%
“…Sickness benefit and welfare support are considered to be the indirect cost of healthcare expenditures [19]. Individuals with HF suffer a variety of emotional and physical symptoms that substantially impair their quality of life (QoL), mobility and daily living [20]. The World Health Organization (WHO) defines QoL as "individuals' perceptions of their position in life in the context of the culture and value systems in which they live and in relation to their goals, expectations, standards and concerns" [21].…”
Section: Socio-economic Challengesmentioning
confidence: 99%